5−8s=1+s−23; s= 8+4t=5−3t−25; t= 7−2x=42+4x−5; x= 5z+7=3−z−14; z= u+3−6u=7−49; u= 3y−7=12−y+13; y= 17−4v=42−v−7; v= 3x−3=9−4x−47; x= 5−4z+9=2z−10; z= 4−2t+5=2t−45; t=
Ответ:
Пошаговое объяснение:
5−8s=1+s−23
-8s-s=1-23-5
-9s=-27
s=3
8+4t=5−3t−25
4t+3t=5-25-8
7t=-28
t=-4
7−2x=42+4x−5
-2x-4x=42-5-7
-6x=30
x=-5
5z+7=3−z−14
5z+z=3-14-7
6z=-18
z=-3
u+3−6u=7−49
u-6u=7-49-3
-5u=-45
u=9
3y−7=12−y+13
3y+y=12+13+7
4y=32
y=8
17−4v=42−v−7
-4v+v=42-7-17
-3v=18
v=-6
3x−3=9−4x−47
3x+4x=9-47+3
7x=-35
5−4z+9=2z−10
-4z-2z=-10-5-9
-6z=-24
z=4
4−2t+5=2t−45
-2t-2t=-45-5-4
-4t=-54
t=13.5
1) 3 2) -4 3) -5 4) -3 5) 9 6) 8 7) -6 8) -5 9) 4 10) Может неправильно написано, но получается 27/2